Content Reordering Based on Mouse-tracking for Web Applications - Md. Tanjim-Al-Akib; Lutfullahil Kabir Ashik; Krishanu Chowdhury; Md. Zahid Hasan; Hosne Al Walid (Advances in Science, Technology and Engineering Systems Journal, 2017)
Rising usage of web applications in every aspect of life has created intense need of enhancement of user experience and formation of intelligent web applications. This research work was conducted with a view to do so. This paper focuses on the reorganization of web application content based on user’s specific interests while browsing any web application by providing new algorithms and a new approach.
Keywords: HCI; Web Application; User experience; User interest; User engagement (UE); Mouse-tracking; User Interest Capturing Algorithm (UICA); Content Reordering Algorithm (CRA)